PENGARUH EMOTIONAL DAN SPIRITUAL QUOTIENT TERHADAP PRESTASI KERJA PEGAWAI BANK SYARIAH MANDIRI CABANG MALANG DIMEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Maulidina, Nur Izzah; Ekowati, Vivin Maharani (Fakultas Ekonomi, UIN Maliki Malang, 2017)
Abstract: This research aims to know the influence of emotional quotient to job performance; the influencespiritual quotient to job performance; to know organizational citizenship behavior mediated emotional quotientand spiritual quotient to job performance. This research was explanatory research. The population in thisstudy are 155 employees of PT Bank Syariah Mandiri Malang and the number of samples are 61 employees.Research results revealed that emotional quotient has no effect directly to job performance; spiritual quotienthas no effect directly to job performance; OCB is not able to mediate emotional quotient to job performanceand OCB was able to mediate the spiritual quotient to job performance.